STRIDE LENGTH AND ITS CORRELATION WITH DYNAMIC BALANCE IN THE ELDERLY WITH KNEE OSTEOARTHRITIS - Nikmatur Rosidah; Raray Inas Prianggalistiari; Anita Faradilla Rahim; Bayu Prastowo (Faculty of Vocational Studies, Universitas Airlangga, 2026)
Background: Patients with knee osteoarthritis experience postural changes that impair balance control due to frequent shifts in the Center of Gravity (COG). Individuals who experience knee osteoarthritis tend to experience a decrease in stride length. A decrease in stride length is also one of the factors that influences the occurrence of balance disorders in the elderly. Purpose: To examine the association between stride length and dynamic balance in patients diagnosed with knee osteoarthritis. Method: This research used an observational cross-sectional study evaluating the correlations between dynamic balance and stride length in knee osteoarthritis patients. Forty-two elderly individuals with knee osteoarthritis were assessed using spatial-temporal stride length and the Short Physical Performance Battery (SPPB) for dynamic balance tests. The Shapiro-Wilk normality test was used to find the data distribution, followed by Spearman correlation coefficients for the correlation test between variables. Result: The study included 42 elderly participants with medically diagnosed knee osteoarthritis (35 females, 7 males. The reported mean age of the respondents is 69 years old, with an average Body Mass Index (BMI) was 25.97 kg/m2. The results were obtained with a Spearman correlation coefficient of r = 0.501 and p-value = 0.001, indicating a statistically significant correlation between stride length and dynamic balance in the elderly with knee osteoarthritis. Conclusion: Stride length is significantly associated with dynamic balance in elderly individuals with knee osteoarthritis. These findings suggest that stride length may serve as a simple and accessible clinical indicator to screen for reduced dynamic balance in patients with knee osteoarthritis.